Grime, gangs and the perpetuation of stereotypes by sportswear brands in the United Kingdom. Issue 1 (1st April 2022) - Parker, Kelly
Sportswear, particularly Nike, has been a fundamental component of the aesthetic of grime since the genre emerged in the United Kingdom in the early 2000s. Whilst grime is primarily known as a genre of electronic music, it can be seen as a multi-faceted creative practice allowing marginalized communities to articulate their antipathy towards existing sociopolitical mores, whilst simultaneously offering alternative sources of income, skills, cohesion and hope. Grime's aesthetic intersects with that of gang culture in several areas including through sportswear. As grime has grown economically brands have noticed ‐ resulting in various collaborations including the 2018 Nike 'Nothing Beats a Londoner' campaign with grime artist Skepta. This article sets out to evaluate this advert and argues that through this collaboration Nike has perpetuated racial stereotyping via culturally appropriating grime culture. In doing so, authentic grime artists have been employed to give the advert greater authenticity, staged in the city that birthed grime. This cultural appropriation has resulted in the perpetuation of dangerous Black male stereotypes, utilizing this to boost sales for the world's largest sport corporation, in stark contrast to the founding principles of grime.